Oral repeated-dose systemic and reproductive toxicity of 6:2 fluorotelomer alcohol in mice. (2015) - Mukerji, Pushkor; Rae, Jessica Caverly; Buck, Robert C.; O'Connor, John C.
Abstract: 6:2 fluorotelomer alcohol (6:2 FTOH) was evaluated for potential systemic repeated-dose and reproductive toxicity in mice. 6:2 FTOH was administered by oral gavage to CD-1 mice as a suspension in 0.5% aqueous methylcellulose with 0.1% Tween-80 at dosages of 1, 5, 25, or 100 mg/kg/day. The no-observed-adverse-effect level (NOAEL) for systemic toxicity was 25 mg/kg/day (males) and 5 mg/kg/day (females), based on effects at higher doses on mortality, clinical observations, body weight, nutritional parameters, hematology (red and white blood cell), clinical chemistry (liver-related), liver weights, and histopathology (liver, teeth, reproductive tract, and mammary gland). However, 6:2 FTOH was not a selective reproductive toxicant. The NOAEL for reproductive toxicity was >100 mg/kg/day; no effects on reproductive outcome were observed at any dosage. The NOAEL for viability and growth of the offspring was 25 mg/kg/day, based on clinical signs of delayed maturation in pups, and reductions in pup survival and pup body weight during lactation at 100 mg/kg/day. While the severity of the effects was generally greater in mice than previously reported in CD rats, the overall NOAELs were identical in both species, 5 mg/kg/day for systemic toxicity and 25 mg/kg/day for offspring viability/growth. 6:2 FTOH was not a selective reproductive toxicant in either species; no effects on reproductive outcome occurred at any dose level, and any effects observed in offspring occurred at dose levels that induced mortality and severe toxicity in maternal animals.